2015
DOI: 10.1272/jnms.82.54
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Maternal Vitamin K Deficiency Associated with Hyperemesis Gravidarum: Its Potential Impact on Fetal Blood Coagulability

Abstract: Vitamin K deficiency is associated with malnutrition in some complications, such as hyperemesis gravidarum, active gastrointestinal diseases, and psychological disorders. Maternal vitamin K deficiency can cause fetal bleeding, in particular, fetal intracranial hemorrhage. Although fetal hemorrhage is uncommon, severe damage to the fetus may be inevitable. We describe a pregnant woman with vitamin K deficiency possibly due to hyperemesis gravidarum. The patient was treated for the deficiency, and no fetal or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 11 publications
1
26
0
Order By: Relevance
“…A fall in Factor VII causes a prolonged PT, with a normal APTT. Prolongation of PT has already been shown in some HG patients [1, 4, 5]. VK administration rapidly ameliorated the prolonged PT in this patient.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…A fall in Factor VII causes a prolonged PT, with a normal APTT. Prolongation of PT has already been shown in some HG patients [1, 4, 5]. VK administration rapidly ameliorated the prolonged PT in this patient.…”
Section: Discussionsupporting
confidence: 54%
“…Although this was not measured in this patient, protein induced by vitamin K absence or antagonist- (PIVKA-) II, a more sensitive marker than PT or PT-INR and is preferred over direct VK measurement, may reveal earlier detection of VK-deficiency, and, thus, its measurement may be considered in patients with HG, especially at the time of surgery. Robinson et al [6], who reported HG-related VK-deficiency-induced maternal hemorrhagic diathesis (epistaxis), recommended that “prophylactic VK replacement should be considered in cases in which HG is severe and protracted.” Another report also supported this view [4]. Although this sounds reasonable, further studies are necessary to determine whether universal prophylactic administration of VK in severe HG patients should be performed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, Corona G et al reported the development of osmotic demyelination syndrome in these patients due to their metabolic disorders and hyponatremia [20]. In another study, Shigemi et al reported that fetal coagulation developed in HG patients due to a vitamin K deficiency [21].…”
Section: Discussionmentioning
confidence: 99%
“…[172]. Malnutrition and vitamin K deficiency might promote HG [173]. The avoidance of substances, odors, or food, which tends to irritate the patient and promote nausea, is considered a supplemental help.…”
Section: Therapymentioning
confidence: 99%